Towards bi-magnetic nanocomposites as permanent magnets through the optimization of the synthesis and magnetic properties of SrFe12O19 nanocrystallites. (20th January 2021) - Maltoni, Pierfrancesco; Sarkar, Tapati; Varvaro, Gaspare; Barucca, Gianni; Ivanov, Sergey A; Peddis, Davide; Mathieu, Roland
Abstract: Sol–gel synthesis was used in order to obtain nanocrystallites of the SrFe12 O19 (SFO) hexaferrite in an efficient and reliable way. By optimizing the initial synthetic conditions, we were able to control the size of the nanoparticles (NPs), at lower annealing temperature. The x-ray powder diffraction, transmission electron microscopy (TEM), and magnetic measurements have demonstrated a significant relation between the morphology, size, and magnetic properties of the nanoscale SFO, revealing a definite dependence on the crystallite size along the c -axis. The obtained NPs appear almost isotropic, in the form of platelets and exhibit similar magnetic performance, in terms of the energy product (BH)MAX, thus, demonstrating the suitability of reducing the annealing temperature without any deterioration in the magnetic properties. Additionally, this work illustrates the feasibility of the sol–gel bottom-up approach to employ magnetic NPs as building-blocks for designing hard/soft exchange-coupled bi-magnetic nanocomposites, combining the high coercivity of a hard phase (SFO) and the high saturation magnetization of a soft phase (CoFe2 O4 ); in this regard, we discuss the tunability of the magnetic anisotropy by symbiotically restricting the growth of both phases.